Loss of Down Syndrome Critical Region-1 Mediated-Hypercholesterolemia Accelerates Corneal Opacity Via Pathological Neovessel Formation. Issue 10 (October 2020) - Muramatsu, Masashi; Nakagawa, Suguru; Osawa, Tsuyoshi; Toyono, Tetsuya; Uemura, Akiyoshi; Kidoya, Hiroyasu; Takakura, Nobuyuki; Usui, Tomohiko; Ryeom, Sandra; Minami, Takashi
Abstract : Objective: The calcineurin-NFAT (nuclear factor for activated T cells)-DSCR (Down syndrome critical region)-1 pathway plays a crucial role as the downstream effector of VEGF (vascular endothelial growth factor)-mediated tumor angiogenesis in endothelial cells. A role for DSCR-1 in different organ microenvironment such as the cornea and its role in ocular diseases is not well understood. Corneal changes can be indicators of various disease states and are easily detected through ocular examinations. Approach and Results: The presentation of a corneal arcus or a corneal opacity due to lipid deposition in the cornea often indicates hyperlipidemia and in most cases, hypercholesterolemia. Although the loss of Apo (apolipoprotein) E has been well characterized and is known to lead to elevated serum cholesterol levels, there are few corneal changes observed in ApoE −/− mice. In this study, we show that the combined loss of ApoE and DSCR-1 leads to a dramatic increase in serum cholesterol levels and severe corneal opacity with complete penetrance. The cornea is normally maintained in an avascular state; however, loss of Dscr-1 is sufficient to induce hyper-inflammatory and -oxidative condition, increased corneal neovascularization, and lymphangiogenesis. Furthermore, immunohistological analysis and genome-wide screening revealed that loss of Dscr-1 in mice triggers increased immune cell infiltration and upregulation of SDF (stromal derived factor)-1 and its receptor, CXCR4 (C-X-C motif chemokine ligand receptor-4), potentiating this signaling axis in the cornea, thereby contributing to pathological corneal angiogenesis and opacity. Conclusions: This study is the first demonstration of the critical role for the endogenous inhibitor of calcineurin, DSCR-1, and pathological corneal angiogenesis in hypercholesterolemia induced corneal opacity. Abstract : Supplemental Digital Content is available in the text.